Laminate film
By optimizing carbon-to-oxygen bond ratios in the laminated film's C1s spectrum, the film achieves strong adhesion of the inorganic layer to the base film, addressing the cost issue associated with nanosilica particles and maintaining adhesion performance.
Patent Information
- Application Number
- JP2023113721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
The use of nanosilica particles in laminated films for enhancing adhesion of inorganic layers increases manufacturing costs, necessitating a cost-effective alternative to ensure strong adhesion without relying on these particles.
A laminated film structure with specific carbon-to-oxygen bond ratios in the C1s spectrum, utilizing a base film and an inorganic layer where the intensity ratios of C-C, C-O, and O=C-O bonds are optimized to enhance chemical interaction, reducing the need for nanosilica particles.
The optimized bond ratios in the laminated film ensure strong adhesion of the inorganic layer to the base film, thereby reducing manufacturing costs while maintaining adhesion performance.
Smart Images

Figure 2025011542000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated film. [Background technology]
[0002] From the viewpoint of weight reduction and high performance of electronic products, various composite materials in which organic materials and inorganic materials are combined have been developed. For example, a laminated film having a base film made of an organic material and an inorganic layer on the base film is known as a composite material. In the manufacturing process of the laminated film, for example, before the inorganic layer is formed on the base film, the surface of the base film is plasma treated to remove dirt and moisture from the surface. Removal of dirt and moisture from the surface of the base film helps to increase the adhesion of the inorganic layer formed on the surface to the base film. Technology related to such laminated films is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 describes a laminated film as an anti-reflection film. This laminated film includes an inorganic layer as an anti-reflection layer and a substrate film supporting the inorganic layer. The substrate film includes a resin film and an HC layer on the resin film. The HC layer contains nanosilica particles. This allows the HC layer to have surface irregularities on the inorganic layer side. According to Patent Document 1, the surface irregularities of the HC layer increase the adhesion of the inorganic layer to the substrate film.
[0005] However, nanosilica particles are relatively expensive and increase the manufacturing costs of the laminated film.
[0006] The present invention provides a laminate film that can ensure adhesion of an inorganic layer to a substrate film while suppressing production costs. [Means for solving the problem]
[0007] The present invention [1] relates to a laminated film comprising a base film and an inorganic layer on the base film, in which in a C1s spectrum at an analysis depth with a carbon element ratio of 25 atom% in an X-ray photoelectron spectroscopy analysis of the inorganic layer in a thickness direction from the side opposite to the base film to the base film side, the intensity Icc of the peak at 285 eV derived from a C-C bond, the intensity Ico of the peak at 286.5 eV derived from a C-O bond, and the intensity Icoo of the peak at 289 eV derived from an O=C-O bond satisfy (Ico+Icoo) / Icc≧0.50.
[0008] The present invention [2] includes the laminate film according to the above [1], in which the intensity Ioc of the peak at 288 eV derived from a C=O bond in the C1s spectrum, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy Ioc / (Icc+Ico+Icoo)≦0.01.
[0009] The present invention [3] includes the laminate film according to the above [1] or [2], in which in the C1s spectrum of the X-ray photoelectron spectroscopy at an analysis depth with a carbon element ratio of 55 atom%, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy (Ico+Icoo) / Icc≧0.80.
[0010] The present invention [4] includes the laminate film according to any one of the above [1] to [3], in which in the C1s spectrum of the X-ray photoelectron spectroscopy at an analysis depth with a carbon element ratio of 55 atom%, the intensity Ioc of the peak at 288 eV derived from a C=O bond, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy Ioc / (Icc+Ico+Icoo)≦0.01.
[0011] The present invention [5] includes the laminate film according to any one of the above [1] to [4], wherein the inorganic layer contains at least one element selected from the group consisting of In, Si, Cr and Nb. Effect of the Invention
[0012] In the laminated film of the present invention, as described above, in the C1s spectrum at an analysis depth of a carbon element ratio of 25 atom% in the X-ray photoelectron spectroscopy analysis in the thickness direction of the inorganic layer from the side opposite to the base film to the base film side, the intensity Icc of the peak (285 eV) derived from the C--C bond, the intensity Ico of the peak (286.5 eV) derived from the C--C bond, and the intensity Icoo of the peak (289 eV) derived from the O=C--C bond satisfy (Ico+Icoo) / Icc≧0.5. This indicates that the chemical interaction between the base film and the inorganic layer is strong. Specifically, this indicates that in the boundary region (interface and its vicinity) between the base film and the inorganic layer, there are relatively many chemical bonds formed between the base film and the inorganic layer via the CO- and O=C-O- moieties of the components derived from the base film (the more such chemical bonds there are, the higher the adhesion of the inorganic layer to the base film). Therefore, the content of particles such as nanosilica particles in the surface layer on the inorganic layer side of the base film can be reduced. This reduces the manufacturing cost of the laminated film. Therefore, according to the laminate film of the present invention, the adhesion of the inorganic layer to the base film can be ensured while suppressing the production cost. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a laminated film of the present invention. [Diagram 2] FIG. 1 shows a laminated film having a laminated structure of an adhesive layer and an antireflection layer as inorganic layers. [Diagram 3] 3 shows an example of a method for producing the laminated film shown in Fig. 1. Fig. 3A shows a cured resin layer forming step, Fig. 3B shows a plasma treatment step, and Fig. 3C shows an inorganic layer forming step. [Figure 4] 2 is a schematic diagram of an apparatus for carrying out a plasma treatment step and a film formation step in the example of the method for producing the laminated film shown in FIG. 1. FIG. [Diagram 5] 5 is a perspective view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. [Figure 6] 5 is a cross-sectional view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. [Figure 7] 1 shows a C1s spectrum at an analysis depth of a carbon element ratio of 25 atom % in an X-ray photoelectron spectroscopy analysis in accordance with Example 1. [Figure 8] 1 shows a C1s spectrum at an analysis depth of a carbon element ratio of 25 atom % in X-ray photoelectron spectroscopy for Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] As shown in Fig. 1, a laminated film X according to one embodiment of the present invention includes a base film 10 and an inorganic layer 20 on the base film 10. Specifically, the inorganic layer 20 is disposed on one surface of the base film 10 in the thickness direction H. The base film 10 and the inorganic layer 20 are in contact with each other. The laminated film X extends in a direction (plane direction D) perpendicular to the thickness direction H.
[0015] The base film 10 has a first surface 10a on the inorganic layer 20 side and a second surface 10b opposite to the first surface 10a. In this embodiment, the base film 10 includes a resin film 11 and a cured resin layer 12 in this order in the thickness direction H. In this embodiment, the resin film 11 and the cured resin layer 12 are in contact with each other. In the base film 10, the cured resin layer 12 forms the first surface 10a, and the resin film 11 forms the second surface 10b.
[0016] The resin film 11 is an element that ensures the strength of the laminated film X. The resin film 11 is, for example, a transparent resin film having flexibility. Examples of the material of the resin film 11 include polyester resin, polyolefin resin, cellulose resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the cellulose resin include triacetyl cellulose (TAC). These materials may be used alone, or two or more types may be used in combination. From the viewpoint of transparency and strength, the material of the resin film 11 is preferably at least one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, and more preferably at least one selected from the group consisting of PET, COP, and TAC. In addition, the resin film 11 does not contain particles in this embodiment.
[0017] The thickness of the resin film 11 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. When the thickness of the resin film 11 is equal to or more than the above lower limit, the strength of the laminated film X can be ensured. When the thickness of the resin film 11 is equal to or less than the above upper limit, the handleability of the base film 10 in the roll-to-roll process described below can be ensured. In addition, a carrier film (not shown) may be attached to the second surface 10b of the resin film 11 in order to ensure the transportability and handleability of the base film 10 in the roll-to-roll process.
[0018] The total light transmittance (JIS K 7375:2008) of the resin film 11 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the resin film 11 is equal to or more than the above lower limit, good transparency can be ensured in the laminate film X.
[0019] The cured resin layer 12 is a functional layer containing a resin. Specifically, the cured resin layer 12 is a cured product of a curable resin composition containing a curable resin. An example of the functional layer is a hard coat layer. The hard coat layer is a layer that makes it difficult for scratches to form on the exposed surface (upper surface in FIG. 1) of the inorganic layer 20.
[0020] Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more. From the viewpoint of ensuring the hardness of the cured resin layer 12, the curable resin is preferably at least one selected from the group consisting of acrylic urethane resin and acrylic resin.
[0021] Examples of the curable resin include ultraviolet curable resin and thermosetting resin. The curable resin is preferably an ultraviolet curable resin. When the curable resin is an ultraviolet curable resin, the curable resin can be cured without high temperature heating, so that the production efficiency of the laminated film X can be improved.
[0022] When the base film 10 has a cured resin layer 12, it is preferable that the cured resin layer 12 contains fewer inorganic oxide particles. The fewer the inorganic oxide particles in the cured resin layer 12, the more the scattering of light incident on the laminated film X caused by particles in the base film 10 can be suppressed, and the manufacturing cost of the laminated film X can be reduced. Examples of materials for inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. The content of inorganic oxide particles in the cured resin layer 12 is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.2% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0.0% by mass.
[0023] The thickness of the cured resin layer 12 is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. When the thickness of the cured resin layer 12 is equal to or more than the above lower limit, the function of the cured resin layer 12 can be ensured. Specifically, when the cured resin layer 12 is a hard coat layer, the scratch resistance of the inorganic layer 20 can be ensured. When the thickness of the cured resin layer 12 is equal to or less than the above upper limit, the transparency of the cured resin layer 12 can be ensured.
[0024] The total light transmittance (JIS K 7375:2008) of the base film 10 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the base film 10 is equal to or more than the above lower limit, good transparency can be ensured in the laminate film X.
[0025] The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the first surface 10a of the base film 10 is preferably 1.0 nm or more, more preferably 1.2 nm or more, even more preferably 1.3 nm or more, and is preferably 10.0 nm or less, more preferably 7.0 nm or less, even more preferably 4.5 nm or less. When the surface roughness Sa of the first surface 10a is equal to or more than the above lower limit, the fine irregularities of the first surface 10a have an anchoring effect on the inorganic layer 20, thereby enhancing adhesion of the inorganic layer 20 to the base film 10. When the surface roughness Sa of the first surface 10a is equal to or less than the above upper limit, excessive irregularities at the interface in the inorganic layer 20 described below can be suppressed.
[0026] In this embodiment, the first surface 10a is a plasma-treated surface. The plasma treatment is a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna, from the viewpoint of increasing the value of the first ratio formula described later (oxygen-LAICP treatment). The oxygen-LAICP treatment of the first surface 10a will be specifically described later with respect to the manufacturing method of the laminated film X.
[0027] The total light transmittance (JIS K 7375:2008) of the laminate film X is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the laminate film X is equal to or more than the above lower limit, the laminate film X can have good transparency.
[0028] Examples of the inorganic layer 20 include an anti-reflective layer and a conductive layer. The anti-reflective layer is a layer having anti-reflective properties that suppresses the reflection intensity of external light. The conductive layer is a layer having conductivity. The inorganic layer 20 may be another layer. The inorganic layer 20 may also be a composite layer including an anti-reflective layer and another layer. The inorganic layer 20 may also be a composite layer including a conductive layer and another layer. FIG. 2 shows a case where the inorganic layer 20 has a laminated structure of an adhesive layer 21 and an anti-reflective layer 22.
[0029] The adhesive layer 21 is disposed on the first surface 10a of the base film 10. Specifically, the adhesive layer 21 is disposed on the cured resin layer 12 of the base film 10. The adhesive layer 21 is in contact with the cured resin layer 12. The adhesive layer 21 is a layer that enhances the adhesiveness of the inorganic layer 20 to the laminated film X. Examples of materials for the adhesive layer 21 include metals such as In, Si, Ni, Cr, Ar, Sn, Au, Ag, Pt, Zn, Ti, W, Zr, Pd, and Nb, alloys of two or more of these metals, and oxides of these metals. From the viewpoint of achieving both the adhesiveness to both the laminated film X and the antireflection layer 22 and the transparency of the adhesive layer 21, the adhesive layer 21 is preferably an inorganic oxide film containing at least one element selected from the group consisting of In, Si, Cr, and Nb. That is, the inorganic layer 20 preferably contains at least one element selected from the group consisting of In, Si, Cr, and Nb. From the viewpoint of achieving both adhesion to both the laminated film X and the antireflection layer 22 and transparency of the adhesion layer 21, indium tin composite oxide (ITO) or silicon oxide (SiOx) is more preferable as the material of the adhesion layer 21. The silicon oxide as the material of the adhesion layer 21 is preferably SiOx having a smaller amount of oxygen than the stoichiometric composition, and more preferably SiOx where x is 1.2 or more and 1.9 or less.
[0030] The thickness of the adhesive layer 21 is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more, and is preferably 50 nm or less, more preferably 30 nm or less, even more preferably 10 nm or less, and even more preferably 5 nm or less. When the thickness of the adhesive layer 21 is equal to or more than the lower limit, the adhesive force between the laminated film X and the antireflection layer 22 can be ensured. When the thickness of the adhesive layer 21 is equal to or less than the upper limit, the transparency of the adhesive layer 21 can be ensured.
[0031] The antireflection layer 22 is disposed on one surface of the adhesive layer 21 in the thickness direction H. The antireflection layer 22 preferably includes a plurality of transparent inorganic oxide films laminated in the thickness direction H. FIG. 2 shows an example of such an antireflection layer 22. The antireflection layer 22 in FIG. 2 includes a high refractive index layer 22a, a low refractive index layer 22b, a high refractive index layer 22c, and a low refractive index layer 22d in this order from the adhesive layer 21 side in the thickness direction H. The high refractive index layer 22a contacts the adhesive layer 21. The high refractive index layer 22a contacts the low refractive index layer 22b. The low refractive index layer 22b contacts the high refractive index layer 22c. The high refractive index layer 22c contacts the low refractive index layer 22d. The high refractive index layers 22a and 22c are layers with a relatively high refractive index, and the low refractive index layers 22b and 22d are layers with a relatively low refractive index. In such a laminated structure, the intensity of the reflected light is attenuated by the interference between the reflected light at multiple interfaces in the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. Such interference can be achieved by adjusting the optical film thickness (the product of the refractive index and the thickness of the film) of each layer in the antireflection layer 22.
[0032] The high refractive index layer 22a (first high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include niobium oxide (Nb2O5), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony tin oxide (ATO). From the viewpoint of achieving both a high refractive index and low absorption of visible light, the high refractive index material is preferably niobium oxide (refractive index 2.33). The optical thickness of the high refractive index layer 22a is, for example, 20 nm or more and, for example, 55 nm or less.
[0033] The low refractive index layer 22b (first low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include silicon dioxide (SiO2) and magnesium fluoride. From the viewpoint of achieving both a low refractive index and low absorption of visible light, the low refractive index material is preferably silicon dioxide (refractive index 1.46). The optical film thickness of the low refractive index layer 22b is, for example, 15 nm or more and, for example, 70 nm or less.
[0034] The high refractive index layer 22c (second high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include the materials described above for the high refractive index layer 22a, and niobium oxide is preferred. The optical thickness of the high refractive index layer 22c is, for example, 60 nm or more and, for example, 330 nm or less.
[0035] The low refractive index layer 22d (second low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include the materials described above for the low refractive index layer 22b, and silicon dioxide is preferred. The optical thickness of the low refractive index layer 22d is, for example, 100 nm or more and, for example, 160 nm or less.
[0036] The total thickness of the antireflection layer 22 is preferably 180 nm or more, more preferably 200 nm or more, and even more preferably 220 nm or more, and is preferably 320 nm or less, more preferably 280 nm or less, and even more preferably 250 nm or less. In this embodiment, the total thickness of the antireflection layer 22 is the sum of the thicknesses of the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. When the total thickness of the antireflection layer 22 is equal to or greater than the lower limit, the antireflection layer 22 can ensure the function of attenuating the reflected light intensity. When the total thickness of the antireflection layer 22 is equal to or less than the upper limit, cracking of the antireflection layer 22 can be suppressed.
[0037] When the inorganic layer 20 includes a conductive layer, the conductive layer is formed from a conductive material. Examples of the conductive material include metals and metal oxides. Examples of the metals include copper, silver, gold, nickel, chromium, and alloys thereof. Examples of the metal oxides include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of the indium-containing conductive oxides include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of the antimony-containing conductive oxides include antimony tin composite oxide (ATO).
[0038] In the C1s spectrum at a predetermined analysis depth in the X-ray photoelectron spectroscopy (XPS) in the thickness direction H from the opposite side of the base film 10 to the base film 10 side of the inorganic layer 20, the intensity of the peak at 285 eV derived from the C-C bond is Icc, the intensity of the peak at 286.5 eV derived from the C-O bond (excluding the C-O bond in the carboxy group) is Ico, the intensity of the peak at 288 eV derived from the C=O bond (excluding the C=O bond in the carboxy group) is Ioc, and the intensity of the peak at 289 eV derived from the O=C-O bond is Icoo. The method of the X-ray photoelectron spectroscopy is specifically as described later in the examples.
[0039] In the above XPS C1s spectrum (first C1s spectrum) for laminate film X at an analysis depth with a carbon element ratio of 25 atom %, the above intensities Icc, Ico, and Icoo of laminate film X satisfy the following formula (1).
[0040] (Ico+Icoo) / Icc≧0.50 (1)
[0041] The numerator of the formula (first ratio formula) on the left side of formula (1) specifically indicates the total ratio of carbon atoms included in C-O bonds (excluding C-O bonds in carboxy groups) and carbon atoms included in O=C-O bonds among the carbon atoms present at the analysis depth of the carbon element ratio of 25 atom% in the above XPS. The larger the value V1 of the first ratio formula, the more CO bonds and O=C-O bonds of the resin component derived from the base film 10 are at the position (first depth position) of the carbon element ratio of 25 atom% in the thickness direction H of the inorganic layer 20. Therefore, the larger the value V1, the more chemical bonds are formed between the base film 10 and the inorganic layer 20 at the first depth position through the CO- and O=C-O portions of the resin component derived from the base film 10. The more such chemical bonds there are, the higher the adhesion of the inorganic layer 20 to the base film 10. In the above XPS for the inorganic layer 20, the analysis depth of the carbon element ratio of 25 atom% is farther from the base film 10 than the analysis depth of the carbon element ratio of 55 atom% described below. The high value V1 of the first ratio equation at such an analysis depth better reflects the strength of the chemical interaction between the substrate film 10 and the inorganic layer 20, compared to the high value V3 of the third ratio equation described below at an analysis depth with a carbon element ratio of 55 atom % described below.
[0042] In the laminated film X, the value V1 of the first ratio formula is 0.50 or more, preferably 0.60 or more, more preferably 0.70 or more. The value V1 is preferably 1.00 or less, more preferably 1.50 or less, and even more preferably 2.00 or less. When the value V1 is equal to or greater than the lower limit, the adhesion of the inorganic layer 20 to the base film 10 can be sufficiently ensured. When the value V1 is equal to or less than the upper limit, it means that the number of C-C bonds in the organic material at the first depth position is greater than a certain level, and therefore the cohesive force of the organic component derived from the base film 10 is sufficiently maintained. When the value V1 is equal to or less than the upper limit, it is preferable to prevent cohesive failure between the base film 10 and the inorganic layer 20.
[0043] In the laminate film X, the intensities Ioc, Icc, Ico, and Icoo in the first C1s spectrum preferably satisfy the following formula (2).
[0044] Ioc / (Icc+Ico+Icoo)≦0.01 (2)
[0045] The denominator of the left-hand side of the formula (2) (second ratio formula) specifically indicates the total ratio of the carbon atoms contained in the CC bond, the carbon atoms contained in the CO bond (excluding the CO bond in the carboxy group), and the carbon atoms contained in the O=CO bond, among the carbon atoms present at the analysis depth of the carbon element ratio of 25 atom% in the XPS. The smaller the value V2 of the second ratio formula, the fewer the C=O bonds of the resin component derived from the base film 10 at the first depth position in the inorganic layer 20. Therefore, a value V2 of 0.01 or less means that at the first depth position, the number of oxygen atoms located at the molecular chain terminals in the organic component derived from the base film 10 is less than a certain level, and therefore, the ratio of oxygen atoms bonded to inorganic atoms in the organic component derived from the base film 10 is greater than a certain level. The value V2 is, for example, 0.00 or more.
[0046] In the above XPS C1s spectrum (second C1s spectrum) for laminate film X at an analysis depth with a carbon element ratio of 55 atom %, the above intensities Icc, Ico, and Icoo of laminate film X satisfy the following formula (3).
[0047] (Ico+Icoo) / Icc≧0.80 (3)
[0048] The numerator of the left-hand side of the formula (3) (third ratio formula) specifically indicates the total ratio of carbon atoms contained in C-O bonds (excluding C-O bonds in carboxy groups) and carbon atoms contained in O=C-O bonds among the carbon atoms present at the analysis depth of the carbon element ratio of 55 atom% in the XPS. The larger the value V3 of the third ratio formula, the more CO bonds and O=C-O bonds of the resin component derived from the base film 10 are at the position (second depth position) of the carbon element ratio of 55 atom% in the thickness direction H of the inorganic layer 20. Therefore, the larger the value V3, the more chemical bonds are formed between the base film 10 and the inorganic layer 20 at the second depth position through the CO- and O=C-O portions of the resin component derived from the base film 10. The more such chemical bonds there are, the higher the adhesion of the inorganic layer 20 to the base film 10.
[0049] In the laminated film X, the value V3 of the third ratio formula is preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more. The value of the third ratio formula is preferably 1.20 or less, more preferably 1.70 or less, and even more preferably 2.20 or less. When the value V3 is equal to or greater than the lower limit, the adhesion of the inorganic layer 20 to the base film 10 can be sufficiently ensured. When the value V3 is equal to or less than the upper limit, it means that the number of C-C bonds in the organic material is more than a certain amount at the second depth position, and therefore the cohesive force of the organic component derived from the base film 10 is sufficiently maintained. When the value V3 is equal to or less than the upper limit, it is preferable to prevent cohesive failure between the base film 10 and the inorganic layer 20.
[0050] The ratio (V1 / V3) of the value V1 of the first ratio formula to the value V3 of the third ratio formula is preferably 0.60 or more, more preferably 0.70 or more, and even more preferably 0.75 or more, and is, for example, 1.00 or less. When the ratio (V1 / V3) is equal to or more than the above lower limit, the adhesion of the inorganic layer 20 to the base film 10 can be sufficiently ensured.
[0051] In the laminate film X, the intensities Ioc, Icc, Ico, and Icoo in the second C1s spectrum preferably satisfy the following formula (4).
[0052] Ioc / (Icc+Ico+Icoo)≦0.01 (4)
[0053] The denominator of the left-hand side of the formula (4) (fourth ratio formula) specifically indicates the total ratio of the carbon atoms contained in the CC bond, the carbon atoms contained in the CO bond (excluding the CO bond in the carboxy group), and the carbon atoms contained in the O=CO bond, among the carbon atoms present at the analysis depth of the carbon element ratio of 55 atom% in the XPS. The smaller the value of the fourth ratio formula, the fewer the C=O bonds of the resin component derived from the base film 10 at the second depth position in the inorganic layer 20. Therefore, a value of 0.01 or less in the fourth ratio formula means that the number of oxygen atoms located at the molecular chain terminals in the organic component derived from the base film 10 at the second depth position is less than a certain level, and therefore means that the ratio of oxygen atoms bonded to inorganic atoms in the organic component derived from the base film 10 is greater than a certain level. The value of the fourth ratio formula is, for example, 0.00 or more.
[0054] The peeling rate of the inorganic layer 20 of the laminated film X in the second test described below after the first test (accelerated weather resistance test) described below is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less, from the viewpoint of ensuring the adhesion of the inorganic layer 20. More specifically, the methods of the first and second tests are as described later in the examples. When the peeling rate of the inorganic layer 20 is equal to or less than the upper limit, the substantial deterioration of the function of the inorganic layer 20 due to peeling of the inorganic layer 20 can be suppressed.
[0055] Test 1: First, the side of the base film 10 of the laminated film X is fixed to a glass plate. Next, the inorganic layer 20 of the laminated film X on the glass plate is irradiated with light at a temperature of 85° C., a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 nm to 450 nm) of 150 mW / cm 2 2 The specimen is exposed to light for 32.5 hours under the above conditions.
[0056] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction are formed with a cutter knife in the inorganic layer 20 of the laminated film X on the glass plate after the first test, and 100 grids are formed by the first and second incisions. Next, isopropyl alcohol is continuously dripped at 2 mL / min on the 100 grid areas of the laminated film X, while a polyester wiper is slid over the area with a wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 0.25 mm out of the 100 grids are cut. 2 The number of squares where the above peeling occurred is counted. The counted number is then divided by 100 to calculate the peeling rate (%).
[0057] 3A to 3C show an example of a method for producing the laminated film X. This production method includes a cured resin layer forming step (FIG. 3A), a plasma treatment step (FIG. 3B), and a film forming step (FIG. 3C).
[0058] In the cured resin layer forming step, as shown in FIG. 3A, a cured resin layer 12' is formed on a long resin film 11. The cured resin layer 12' can be formed by applying the above-mentioned curable resin composition on the substrate film 11 to form a coating film, and then curing the coating film. The curable resin composition may contain other components other than the above-mentioned curable resin as necessary. Examples of the other components include a solvent and a leveling agent. Examples of the solvent include butyl acetate, ethyl acetate, toluene, and cyclopentanone. When the curable resin composition contains an ultraviolet-curable resin as the curable resin, the curable resin composition preferably contains a photopolymerization initiator. When the curable resin composition contains a thermosetting resin as the curable resin, the curable resin composition preferably contains a thermal polymerization initiator.
[0059] When the curable resin composition contains a solvent, the coating film on the resin film 11 is dried after the application of the curable resin composition. The drying temperature is, for example, 50° C. or higher and, for example, 120° C. or lower. The drying time is, for example, 10 seconds or longer and, for example, 10 minutes or shorter.
[0060] When the curable resin composition contains an ultraviolet-curable resin, the coating film on the resin film 11 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The cumulative irradiation amount of the ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.
[0061] When the curable resin composition contains a thermosetting resin, the coating on the resin film 11 is cured by heating. The heating temperature is, for example, 100° C. or more and, for example, 150° C. or less. The heating time is, for example, 10 seconds or more and, for example, 10 minutes or less.
[0062] In this manner, a long substrate film 10' is obtained. The first surface 10a' of the substrate film 10' on the side of the cured resin layer 12' is the surface before the plasma treatment described below. In this embodiment, a roll of the long substrate film 10' is prepared. Specifically, the substrate film 10' is wound so that the first surface 10a' of the substrate film 10' faces inward in the roll radial direction.
[0063] In this manufacturing method, next, a plasma treatment process and a film formation process are carried out in sequence while the base film 10' is transported as a workpiece film W in a roll-to-roll manner under a reduced pressure atmosphere. The device Y shown in Fig. 4 is an example of a device for carrying out the plasma treatment process and the film formation process. The device Y includes a payout chamber R1, a winding chamber R2, a connection chamber C1, a plasma treatment chamber C2, a connection chamber C3, a film formation chamber C4, a connection chamber C5, a connection chamber C6, and a PEM device (not shown).
[0064] The pay-out chamber R1 is equipped with a pay-out roller 51 for paying out the workpiece film W. A roll of a long base film 10' is attached to the pay-out roller 51 as the workpiece film W. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the pay-out chamber R1.
[0065] The winding chamber R2 is equipped with a winding roller 52 for winding up the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the winding chamber R2.
[0066] The connecting chamber C1 is disposed next to the pay-out chamber R1 in the running direction of the workpiece film W, and disposed before the plasma processing chamber C2. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C1. The connecting chamber C1 is connected to a vacuum pump (not shown), and is configured so that the pressure inside the connecting chamber C1 can be adjusted. When the device Y is in operation, the pressure inside the connecting chamber C1 is maintained at a predetermined pressure between the pressure inside the pay-out chamber R1 and the pressure inside the plasma processing chamber C2. This ensures a pressure difference between the pay-out chamber R1 and the plasma processing chamber C2.
[0067] The plasma processing chamber C2 is disposed between the connecting chamber C1 and the connecting chamber C3 in the running direction of the workpiece film W. In the plasma processing chamber C2, a plasma processing step is carried out as described below.
[0068] In this embodiment, the plasma processing chamber C2 is equipped with a plurality of low inductance antennas (LA) 71. The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and can generate inductively coupled plasma by applying high frequency power. In this embodiment, the LA 71 is supported by a mounting fixture 72 and covered by a cover block 73 (not shown in FIG. 5) as shown in FIG. 5 and FIG. 6, and is disposed inside the plasma processing chamber C2 (a case where the number of LA 71 is four is illustrated as an example).
[0069] The multiple LAs 71 are arranged in a line in the running direction of the base film 10 and in a direction perpendicular to the running direction (the width direction of the base film 10). The fixture 72 is a vacuum flange. The LAs 71 are fixed to the fixture 72 via a feedthrough 74 as shown in FIG. 6. The fixture 72 is assembled to an opening 75 provided in the wall of the plasma processing chamber C2 as shown in FIG. 4. Specifically, the fixture 72 is assembled to the opening 75 with a seal member (not shown) sandwiched between the wall of the plasma processing chamber C2 and the fixture 72. The LAs 71 are electrically connected to a high-frequency power source (RF power source) outside the plasma processing chamber C2 via an impedance matching device. Such an LAs 71 is formed of a conductor. Examples of the conductor include copper and silver, and copper is preferable. The LAs 71 may be covered with an insulator. Examples of the insulator include glass and quartz.
[0070] The cover block 73 includes a block body 73A and a plurality of partition plates 73B. The block body 73A has a plurality of storage spaces 73a. Each storage space 73a stores one LA 71. The partition plates 73B are arranged to close the storage spaces 73a. The storage spaces 73a are sealed spaces. In the cover block 73, the block body 73A is made of, for example, aluminum. Examples of aluminum include aluminum A5052. The partition plates 73B are made of an insulating material. Examples of insulating materials include quartz and glass. The separation distance d' (shown in FIG. 6) between the base film 10 traveling in the plasma processing chamber C2 and the cover block 73 is, for example, 50 to 200 mm. Such a cover block 73 helps to avoid damage and contamination of the LA 71 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the LA 71, and also helps to suppress damage to the substrate film 10 being plasma processed.
[0071] As shown in FIG. 5, the LA71 has an open loop shape in this embodiment. The open loop shape of the LA71 is advantageous in lowering the inductance of the LA71. Therefore, the open loop shape of the LA71 can suppress an increase in voltage due to an increase in the power applied to the LA71. This can suppress abnormal discharge during plasma processing, which will be described later. Suppression of abnormal discharge can suppress damage to the workpiece film W being plasma processed. Specifically, the LA71 has a U-shape having two free ends. For each LA71, the two free ends are fixed to the fixture 72 so as to be aligned in the width direction of the workpiece film W. In addition, in this embodiment, the LA71 has an extension portion 71a on the opposite side to the two free ends. The extension portion 71a extends parallel to the workpiece film W passing through the plasma processing chamber C2. Each extension portion 71a extends in the width direction of the workpiece film W. Each extension 71a may extend in the running direction of the workpiece film W (four LAs 71 may be arranged in this manner). The length of the extension 71a is, for example, 50 to 150 mm (FIG. 5 illustrates an example in which the length of the extension 71a is the same as the maximum length d2 of the LA71, which will be described later). The LA71 may have a coil shape instead of an open loop shape.
[0072] The LA 71 extends from the fixture 72 toward the base film 10. The LA 71 preferably extends in a direction perpendicular to the fixture 72. The extension length d1 of the LA 71 from the fixture 72 is, for example, 30 to 150 mm. The maximum length d2 of the LA 71 in the surface direction of the base film 10 is, for example, 50 to 150 mm. The separation distance d3 (shown in FIG. 6) between the LA 71 and the base film 10 is, for example, 50 to 200 mm. The extension length d1 and the separation distance d3 are preferably the same. The ratio (d3 / d1) of the separation distance d3 to the extension length d1 is, for example, 0.5 to 3.5. The number (number of rows) of the LA 71 arranged at a distance in the running direction of the base film 10 may be 1, 2, or 3 depending on the running speed of the base film 10 (i.e., the plasma treatment time), or may be 4 or more if necessary. In the running direction of the base film 10, the center distance d4 between adjacent LAs 71 is, for example, 100 to 500 mm. In the width direction of the base film 10, the center distance d5 between adjacent LAs 71 is, for example, 200 to 500 mm. By adjusting the center distance d5, the uniformity of the plasma density in the width direction of the base film 10 described later can be controlled. The center distance d4 and the center distance d5 are preferably the same. The ratio (d5 / d4) of the center distance d5 to the center distance d4 is, for example, 0.5 to 2.0. The center points of the extensions 71a of the four LAs 71 preferably form a square with the vertices as vertices. Such a set of LAs 71 can generate high-density plasma. For the LAs 71, for example, a high-frequency antenna for plasma generation described in JP 2013-258153 A may be used.
[0073] In this embodiment, the plasma processing chamber C2 further includes a transport roller 53. The transport roller 53 is a main guide roller for transporting the workpiece film W in the plasma processing chamber C2. The transport roller 53 has a temperature adjustment function that can heat or cool the workpiece film W. That is, the transport roller 53 is a transport roller with a temperature adjustment function. When the device Y is in operation, the transport roller 53 transports the base film 10 while contacting the second surface 10b of the base film 10. The LA71 is disposed opposite the transport roller 53. According to the device Y including such a plasma processing chamber C2, in the plasma processing step S2, the transport roller 53 with a temperature adjustment function that contacts the base film 10 can perform plasma processing on the base film 10 while cooling or heating the base film 10. By controlling the temperature of the base film 10, thermal deformation of the base film 10 can be suppressed, and the influence of the thermal deformation on the transport of the base film 10 can be suppressed.
[0074] The PEM device is a device for performing plasma emission monitoring (PEM) during plasma processing, and includes a device body and an optical fiber for collecting light. The tip (one end) of the optical fiber is disposed between the workpiece film W and the LA71 in the direction of separation between them in the plasma processing chamber C2. The other end of the optical fiber is connected to the device body. In addition, a first line L1 with a flow rate control valve for introducing gas into the chamber is connected to the plasma processing chamber C2.
[0075] The connecting chamber C3 is disposed next to the plasma processing chamber C2 in the running direction of the workpiece film W and disposed before the film forming chamber C4. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C3. The connecting chamber C3 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the chamber. When the device Y is in operation, the pressure inside the connecting chamber C3 is maintained at a predetermined pressure between the pressure inside the plasma processing chamber C2 and the pressure inside the film forming chamber C4. This ensures a pressure difference between the plasma processing chamber C2 and the film forming chamber C4.
[0076] The film-forming chamber C4 is disposed next to the connection chamber C3 in the running direction of the workpiece film W. The film-forming chamber C4 is connected to a vacuum pump (not shown) and is configured to be able to adjust the interior of the chamber to a predetermined vacuum level. In the film-forming chamber C4, a film-forming process is carried out as described below.
[0077] In this embodiment, the film forming chamber C4 is a sputtering film forming chamber. The film forming chamber C4 includes a film forming roller 54 and a plurality of sputtering chambers 60 (sputtering chambers 60a to 60e) (a case where the number of sputtering chambers 60 is 5 is illustrated as an example). The film forming roller 54 is a main guide roller for transporting the workpiece film W in the film forming chamber C4. The film forming roller 54 has a temperature adjustment function capable of heating or cooling the workpiece film W. The sputtering chamber 60 is a space partitioned in the film forming chamber C4. The plurality of sputtering chambers 60 are arranged along the circumferential direction of the film forming roller 54. Each sputtering chamber 60 opens toward the film forming roller 54. A cathode 61 is provided in the sputtering chamber 60. A target (not shown) is arranged on the cathode 61 as a film forming material supply material. The target is arranged on the target so as to face the film forming roller 54. Each sputtering chamber 60 is provided with a power supply (not shown) for applying a voltage to the target to generate a glow discharge. Examples of power supplies include a DC power supply, an AC power supply, an MF power supply, an RF power supply, and an MF-AC power supply. An MF-AC power supply refers to an AC power supply with a frequency band of several kHz to several MHz. A required number of second lines (not shown) with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber 60. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the film formation chamber C4.
[0078] The connecting chamber C5 and the connecting chamber C6 are arranged in this order between the film forming chamber C4 and the winding chamber R2 in the running direction of the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C5. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C6. The connecting chamber C5 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. The connecting chamber C6 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. When the device Y is in operation, the pressure inside the connecting chambers C5 and C6 is maintained at a predetermined pressure between the pressure inside the film forming chamber C4 and the pressure inside the winding chamber R2. This ensures a pressure difference between the film forming chamber C4 and the winding chamber R2.
[0079] A plasma processing step and a film forming step are carried out in sequence by the above-described apparatus Y. Specifically, the steps are as follows.
[0080] The workpiece film W is unwound from the unwinding chamber R1. After being unwound from the unwinding chamber R1, the workpiece film W passes through the connecting chamber C1, the plasma processing chamber C2, the connecting chamber C3, the film forming chamber C4, the connecting chamber C5, and the connecting chamber C6 in sequence, and is wound up in the winding chamber R2. The running speed of the workpiece film W is, for example, 0.5 m / min or more, and, for example, 5 m / min or less. In addition, the series of lines from the unwinding chamber R1 to the winding chamber R2 is not open to the atmosphere along the way, and the process is carried out in the line under a reduced pressure atmosphere. The reduced pressure atmosphere is preferably under vacuum. Under vacuum preferably means a reduced pressure atmosphere of 7 Pa or less.
[0081] In the plasma processing chamber C2, a plasma processing step is carried out. In the plasma processing step, in a reduced pressure atmosphere in the plasma processing chamber C2 (chamber), the workpiece film W is plasma-processed while detecting the plasma emission intensity. In this embodiment, the plasma processing is a process using inductively coupled plasma of an oxygen-containing gas (oxygen-LAICP process) generated by applying high-frequency power to the LA71. Specifically, it is as follows.
[0082] Oxygen is supplied into the plasma processing chamber C2 during plasma processing through the first line L1. In addition to oxygen, an inert gas may be supplied into the plasma processing chamber C2. Examples of the inert gas include argon, krypton, and xenon. The gas in the plasma processing chamber C2 may contain other gases besides the inert gas. Examples of the other gases include oxygen, nitrogen, hydrogen, and water vapor. The oxygen concentration of the gas (oxygen-containing gas) in the plasma processing chamber C2 is preferably 30% by volume or more, more preferably 50% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume. When the oxygen concentration is equal to or more than the lower limit, a high-density oxygen plasma can be generated. This is useful for forming nanometer-order fine irregularities on the surface of the workpiece film W and for highly activating the surface by cleaning it.
[0083] The pressure (first pressure) in the plasma processing chamber C2 during plasma processing is preferably 0.1 Pa or more, more preferably 0.2 Pa or more, even more preferably 0.3 Pa or more, and is preferably 7 Pa or less, more preferably 5 Pa or less, even more preferably 3 Pa or less. When the first pressure is equal to or greater than the above-mentioned lower limit, a plasma environment of sufficient density for surface modification processing of the workpiece film W can be formed in the plasma processing chamber C2 in the plasma processing. When the first pressure is equal to or less than the above-mentioned upper limit, damage to the workpiece film W caused by excessively high-density plasma can be suppressed in the plasma processing. The first pressure can be adjusted by the amount of oxygen gas supplied into the plasma processing chamber C2.
[0084] The frequency of the high frequency power applied to the LA71 during plasma processing is preferably 1 MHz or more, more preferably 5 MHz or more, and even more preferably 10 MHz or more, and is also preferably 100 MHz or less, more preferably 80 MHz or less, and even more preferably 60 MHz or less. When the frequency is equal to or more than the lower limit, the plasma discharge can be stabilized while increasing the plasma current density in the plasma processing. When the frequency is equal to or less than the upper limit, the antenna potential can be suppressed, and therefore damage to the workpiece film W caused by the plasma can be suppressed. Moreover, the high frequency power is preferably 0.1 kW or more, more preferably 0.3 kW or more, and even more preferably 1.0 kW or more, and is also preferably 10 kW or less, more preferably 8 kW or less, and even more preferably 6 kW or less. When the high frequency power is equal to or more than the lower limit, a high density plasma environment can be formed in the plasma processing chamber C2 in the plasma processing by inductively coupled plasma. When the high frequency power is equal to or less than the upper limit, excessive damage to the workpiece film W caused by the plasma can be suppressed.
[0085] In the plasma treatment step, the plasma emission intensity during the plasma treatment is preferably monitored by a PEM device, and the amount of oxygen gas introduced, the high frequency power, the travel speed, and the like are controlled based on the monitoring results.
[0086] In the plasma treatment process, the plasma current density at the intermediate position between the LA71 and the workpiece film W is preferably 1.0 mA / cm 3 More preferably, 2.0 mA / cm 3 More preferably, 3.0 mA / cm 3 More than 10 mA / cm 3 Less than or equal to 8mA / cm 3 Less than 4 mA / cm, more preferably 3The following is the results. Inductive coupling type plasma processing using a low inductance antenna can achieve a higher plasma current density (for example, a plasma density about 100 times higher) than the capacitive coupling type plasma processing. When the plasma current density is equal to or higher than the lower limit, sufficient plasma oxygen particles can be secured in the plasma processing chamber C2 during plasma processing, and the surface of the workpiece film W can be appropriately modified. When the plasma current density is equal to or lower than the upper limit, damage to the workpiece film W caused by excessively high density plasma oxygen particles can be suppressed during plasma processing. Methods for adjusting the plasma current density include, for example, adjusting the amount of oxygen gas introduced into the plasma processing chamber C2, adjusting the frequency of the high frequency power in the high frequency power supply, and adjusting the magnitude of the applied power.
[0087] By subjecting the substrate film 10' (FIG. 3A) to the above-described plasma treatment, a substrate film 10 having a cured resin layer 12 is obtained as shown in FIG. 3B. The substrate film 10 has a first surface 10a that has been subjected to the oxygen-LAICP treatment as described above. The oxygen-LAICP treatment enhances the activity of the surface of the cured resin layer 12. Specifically, the oxygen-LAICP treatment forms C-O bonds from some of the multiple C-C bonds on the surface of the cured resin layer 12, and forms O-C-O bonds from some of the multiple C-O bonds.
[0088] In the film formation process, following the plasma treatment process, an inorganic layer 20 is formed on the workpiece film W (base film 10) by sputtering in a reduced pressure atmosphere as shown in Fig. 3C. Specifically, the inorganic layer 20 is formed on the cured resin layer 12 whose surface has been highly activated as described above. The reduced pressure atmosphere is preferably a vacuum.
[0089] In the sputtering method, a sputtering gas (inert gas) is introduced into each sputtering chamber 60 through one second line, while a negative voltage is applied to a target (film forming material) arranged on a cathode 61 in the sputtering chamber 60. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and depositing the ejected target material on the workpiece film W. Examples of sputtering gases include argon, krypton, and xenon.
[0090] When the deposition material is a metal oxide, the sputtering method may be a reactive sputtering method. In the reactive sputtering method, oxygen (reactive gas) is introduced into the sputtering chamber 60 in addition to the sputtering gas. The oxygen is introduced into the sputtering chamber 60 through another second line. In the reactive sputtering method, the target is made of, for example, a metal in the metal oxide that forms each layer.
[0091] In the sputtering method, the pressure (second pressure) in the sputtering chamber 60 is, for example, 0.1 to 5.0 Pa depending on the type of layer to be formed. The film formation temperature (the temperature of the workpiece film W adjusted by the film formation roller 54) is, for example, -10°C to 150°C.
[0092] In the film formation step, specifically, the inorganic layer 20 is formed on the cured resin layer 12 by a sputtering method in at least one sputtering chamber selected from the sputtering chambers 60a to 60e. For example, when manufacturing the laminated film X shown in Fig. 2, the adhesive layer 21 is formed on the cured resin layer 12 in the sputtering chamber 60a, the high refractive index layer 22a is formed on the adhesive layer 21 in the sputtering chamber 60b, the low refractive index layer 22b is formed on the high refractive index layer 22a in the sputtering chamber 60c, the high refractive index layer 22c is formed on the low refractive index layer 22b in the sputtering chamber 60d, and the high refractive index layer 22d is formed on the high refractive index layer 22c in the sputtering chamber 60e.
[0093] In the device Y, after the plasma treatment process and the film forming process, the laminated film X as the workpiece film W passes through the connecting chambers C5 and C6 and reaches the winding chamber R2, where it is wound up by the winding roller 52.
[0094] In this manner, a long laminate film X can be produced.
[0095] In the laminated film X, as described above, in the C1s spectrum at an analysis depth of a carbon element ratio of 25 atom% in the X-ray photoelectron spectroscopy analysis in the thickness direction H of the inorganic layer 20 from the side opposite to the base film 10 to the base film 10 side, the intensity Icc of the peak derived from the C-C bond, the intensity Ico of the peak derived from the C-O bond, and the intensity Icoo of the peak derived from the O=C-O bond satisfy (Ico+Icoo) / Icc≧0.5. This indicates that the chemical interaction between the base film 10 and the inorganic layer 20 is strong. Specifically, it indicates that in the boundary region (interface and its vicinity) between the base film 10 and the inorganic layer 20, there are relatively many chemical bonds formed between the base film 10 and the inorganic layer 20 via the CO- and O=C-O- moieties of the resin component derived from the base film 10. By forming the inorganic layer 20 after performing the oxygen-LAICP treatment on the surface of the base film 10 as described above, such a boundary region can be formed, and the adhesion of the inorganic layer to the base film 10 can be improved. This makes it possible to reduce the content of particles such as nanosilica particles in the surface layer on the inorganic layer 20 side of the base film 10. This allows the production cost of the laminated film X to be reduced.
[0096] Therefore, with the laminate film X, the adhesion of the inorganic layer 20 to the base film 10 can be ensured while keeping production costs down. EXAMPLES
[0097] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0098] Example 1 The laminated film of Example 1 was produced by carrying out the following steps in order.
[0099] First, a hard coat layer was formed on one side of a triacetyl cellulose (TAC) film as a resin film to prepare a substrate film (cured resin layer forming process). Specifically, first, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of an ultraviolet-curable acrylic urethane resin (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to prepare a first resin composition with a solid content concentration of 75% by mass. Next, cyclopentanone was added as an additional solvent to the first resin composition to prepare a second resin composition with a solid content concentration of 50% by mass. Meanwhile, a long TAC film (length 100 m, width 340 mm, thickness 40 μm) was prepared. Next, the second resin composition was applied to one side of the TAC film to form a coating film. Next, this coating film was dried by heating and then cured by ultraviolet light irradiation. As a result, a hard coat (HC) layer having a thickness of 5 μm was formed on the TAC film. The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet light irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet light with a wavelength of 365 nm was irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm. 2 In this manner, a TAC film with an HC layer was prepared as a substrate film.
[0100] Next, while the base film was transported in a vacuum by a roll-to-roll method, a plasma treatment process and a subsequent film formation process were performed on the base film (roll-to-roll process). For the plasma treatment process and the film formation process, an apparatus (first apparatus) capable of performing a roll-to-roll process on the work film was used. The first apparatus includes a payout chamber, a plasma treatment chamber, a film formation chamber, and a winding chamber. The payout chamber, the plasma treatment chamber (first plasma treatment), the film formation chamber, and the winding chamber are arranged in this order and communicate with each other. The payout chamber includes a payout roller. A roll of the base film was set on the payout roller as the work film. The plasma treatment chamber includes a transport roller with a temperature control function (transport roller 53 in FIG. 4) and four low inductance antennas (LA71 in FIG. 5 and FIG. 6) covered with a cover block (cover block 73 in FIG. 6) as shown in FIG. 5 and FIG. 6. Each low inductance antenna has an extension portion (extension portion 71a in FIG. 5) parallel to the base film. In the four low inductance antennas, the extension length d1 is 88 mm, the maximum length d2 (length of the extension portion) is 100 mm, the separation distance d3 is 112 mm, the center distance d4 is 290 mm, and the center distance d5 is 280 mm (FIGS. 5 and 6). Each low inductance antenna is electrically connected to a high frequency power source (RF power source, frequency 13.56 MHz) via an impedance matching device outside the plasma processing chamber. The separation distance d' between the base film traveling in the plasma processing chamber and the cover block is 100 mm. In addition, the film formation chamber is a sputtering film formation chamber, and includes a film formation roller (film formation roller 54 in FIG. 4) and first and second sputtering chambers (sputtering chambers 60a, 60b in FIG. 4). Each sputtering chamber is a space partitioned within the film formation chamber. The first and second sputtering chambers are arranged in this order along the circumferential direction of the deposition roller and in the running direction of the base film. Each sputtering chamber has a cathode arranged opposite the deposition roller. A required number of second lines (not shown) equipped with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber. The winding chamber has a winding roller.
[0101] In the roll-to-roll process, the HC surface (first surface) of the base film was plasma-treated in the plasma treatment chamber (plasma treatment step). The running speed of the base film (film running speed) was 1.0 m / min. The temperature of the temperature-adjustable transport roller was -8°C. The plasma treatment conditions were as follows:
[0102] The ultimate vacuum level of the plasma processing chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure inside the plasma treatment chamber reached 0.5 Pa, oxygen gas was introduced into the plasma treatment chamber to set the pressure inside the plasma treatment chamber to 0.5 Pa. By applying high frequency power of 5.0 kW from a high frequency power supply to four low inductance antennas, inductively coupled plasma of an oxygen-containing gas was formed around the antennas (the surface of the HC layer of the base film was treated with this plasma).
[0103] In the deposition chamber, an ITO layer and a SiO2 layer were successively formed on the substrate film after the plasma treatment (deposition process). Specifically, while the substrate film was cooled and transported by the deposition roll in the deposition chamber, an ITO layer was formed on the HC layer of the substrate film in the first sputtering chamber, and a SiO2 layer was formed on the ITO in the second sputtering chamber. The deposition temperature (temperature of the deposition roll) was set to -8°C. More specifically, it is as follows.
[0104] In the first sputtering chamber, a 5 nm thick ITO layer was formed as the first inorganic layer by sputtering (ITO layer formation process). In this process, the ultimate vacuum in the film formation chamber was 1.0×10 -4 After the chamber was evacuated to a vacuum of 0.3 Pa, argon was introduced as an inert gas into the first sputtering chamber, and the pressure in the first sputtering chamber was set to 0.3 Pa. As the target, a sintered body of indium oxide and tin oxide (ITO with a tin oxide concentration of 10 mass %) was used. As the power source for applying a voltage to the target, a DC power source was used. The discharge power was 1.0 kW.
[0105] In the second sputtering chamber, a 20 nm thick SiO2 layer was formed as the second inorganic layer by reactive sputtering (SiO2 layer formation process). In this process, after the deposition chamber was evacuated as described above, argon as an inert gas and oxygen as a reactive gas were introduced into the second sputtering chamber, and the pressure in the second sputtering chamber was set to 0.3 Pa. The amount of oxygen introduced per 100 volume parts of argon introduced into the second sputtering chamber was 30 volume parts. A Si target was used as the target. A MF-AC power supply (60 kHz) was used as the power supply for applying a voltage to the target. The discharge power was 3.0 kW.
[0106] In the above manner, the laminated film of Example 1 was produced. The laminated film of Example 1 includes a substrate film with an HC layer and an inorganic layer (ITO layer / SiO2 layer) on the HC layer. The substrate film of the laminated film of Example 1 has a plasma-treated HC layer surface. This plasma treatment is a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-LAICP treatment).
[0107] Comparative Example 1 First, an HC layer was formed on one surface of a TAC film in the same manner as in the cured resin layer forming step in Example 1. In this way, a base film (TCA film / HC layer) was obtained.
[0108] Next, while the base film was transported in a vacuum by a roll-to-roll method, a plasma treatment process and a subsequent film formation process were performed on the base film (roll-to-roll process). A second device capable of performing a roll-to-roll process on the work film was used for the plasma treatment process and the film formation process. The second device has the same configuration as the first device, except that it has a second plasma treatment chamber instead of the first plasma treatment. The second plasma treatment chamber has a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304) as a pair of flat electrodes for generating plasma. The pair of flat electrodes are arranged parallel to the base film passing through the second plasma treatment chamber with a gap of 50 mm between them. The anode electrode is arranged at a position 35 mm away from the base film passing through the plasma treatment chamber and is grounded outside the plasma treatment chamber. The cathode electrode is arranged so as to face the HC layer surface of the base film, and is electrically connected to a high-frequency power source (RF power source, 13.56 MHz) via an impedance matching device. The length of each electrode facing the base film in the film running direction is 110 mm, and the length in the width direction is 430 mm.
[0109] In the roll-to-roll process, the HC surface (first surface) of the base film was plasma-treated (bombardment treatment) in the second plasma treatment chamber. The running speed of the base film (film running speed) was 1.0 m / min. The conditions for the plasma treatment were as follows:
[0110] The ultimate vacuum in the second plasma processing chamber is 1.0×10 -4 After evacuating the inside of the device until the pressure reached 0.5 Pa, argon was introduced into the second plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 0.5 Pa. Capacitively coupled plasma (CCP) was generated by applying 700 W of power between the planar electrodes using a high-frequency power source. In this plasma environment, argon ion bombardment treatment (Ar-BB treatment) was performed on the surface of the HC layer of the base film.
[0111] In the film formation chamber, an ITO layer and a SiO2 layer were formed in sequence on the substrate film after the plasma treatment in the same manner as described above in relation to Example 1.
[0112] In this manner, the laminated film of Comparative Example 1 was produced. The laminated film of Comparative Example 1 includes a substrate film with an HC layer and an inorganic layer (ITO layer / SiO2 layer) on the HC layer. The substrate film of the laminated film of Comparative Example 1 has a plasma-treated HC layer surface. This plasma treatment is an ion bombardment treatment (Ar-BB treatment) by capacitively coupled plasma using argon-containing gas.
[0113] <X-ray photoelectron spectroscopy analysis> The depth profile of elemental composition ratio (atom %) (elemental composition ratio according to depth) was measured by X-ray photoelectron spectroscopy for the inorganic layers in each laminate film of Example 1 and Comparative Example 1. Specifically, the results are as follows.
[0114] The sample for analysis was prepared by cutting out a piece measuring 10 mm x 10 mm from the center in the width direction of the laminated film. An X-ray photoelectron spectrometer (product name "KRATOS ULTRA2", manufactured by Shimadzu Corporation) was used for the analysis. In the analysis, ion etching of the inorganic layer from the side opposite the substrate film and X-ray photoelectron spectroscopy (XPS) under the following conditions were repeated alternately. For ion etching, Ar gas cluster ions (Ar n + ) was used. In this analysis, the carbon element ratio gradually increased as the analysis position in the thickness direction of the inorganic layer became deeper. In this analysis, narrow scan analysis of the C1s spectrum was performed at a depth position (first depth position) where the carbon element ratio was 25 atom%, and narrow scan analysis of the C1s spectrum was performed at a depth position (second depth position) where the carbon element ratio was 55 atom%.
[0115] [XPS conditions] Excitation X-ray source: Monochrome AI Kα X-ray Setting:700μm×300μm(5mA,75W) Photoelectron take-off angle: 90° to the sample surface Neutralization conditions: Use of neutralization gun and Ar ion gun (neutralization mode) Bond energy correction: The peak due to the CC bond in the C1s spectrum is corrected to 285.0 eV.
[0116] Then, for each depth position, the intensity (Icc) of the peak at 285 eV due to the C-C bond, the intensity (Ico) of the peak at 286.5 eV due to the C-O bond, the intensity (Ioc) of the peak at 288 eV due to the C=O bond, and the intensity (Icoo) of the peak at 289 eV due to the O=C-O bond were calculated based on the results of the narrow scan analysis. The intensities Icc, Ico, Ioc, and Icoo at the first depth position, the value V1 of (Ico+Icoo) / Icc as the first ratio, and the value of Ioc / (Icc+Ico+Icoo) are shown in Table 1. The intensities Icc, Ico, Ioc, and Icoo at the second depth position, the value V3 of (Ico+Icoo) / Icc as the third ratio, and the value of Ioc / (Icc+Ico+Icoo) are also shown in Table 1. The ratio (V1 / V3) of the value V1 of the first ratio formula to the value V3 of the third ratio formula is also shown in Table 1. FIG. 7 shows the C1s spectrum at a depth position where the carbon element ratio is 25 atom% in the inorganic layer of the laminated film of Example 1. FIG. 8 shows the C1s spectrum at a depth position where the carbon element ratio is 25 atom% in the inorganic layer of the laminated film of Comparative Example 1. In each spectrum, the horizontal axis represents the binding energy (eV) of the photoelectrons observed in XPS, and the vertical axis represents the normalized emission intensity (normalized intensity). In FIG. 7 and FIG. 8, the positions where the binding energies are 285 eV, 286.5 eV, 288 eV, and 289 eV are shown by dashed lines.
[0117] <Adhesion> For each of the laminate films of Example 1 and Comparative Example 1, the following first and second tests were carried out to examine the adhesion of the inorganic layer.
[0118] Test 1: First, the substrate film side of the laminated film was fixed to a glass plate. Next, the inorganic layer of the laminated film on the glass plate was irradiated with light at a temperature of 85° C., a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 nm to 450 nm) of 150 mW / cm 2 2 The specimen was exposed to light from a metal halide lamp for 32.5 hours under the above conditions (accelerated weather resistance test). This test was carried out using Iwasaki Electric's "Eye Super UV Tester SUV-W161."
[0119] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction were made with a cutter knife in the inorganic layer and adhesive layer of the laminated film on the glass plate after the first test, and 100 grids were formed by the first and second incisions. Next, isopropyl alcohol was continuously dripped at 2 mL / min on the 100 grid areas of the laminated film while a polyester wiper (trade name "Anticon Gold", manufactured by Sanplatec Co., Ltd.) was slid over the wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 0.25 mm out of the 100 grids were cut. 2 The number of squares in which the above peeling occurred was counted, and the counted number was then divided by 100 to calculate the peeling rate (%).
[0120] A peeling rate of 5% or less was evaluated as "good", and a peeling rate of more than 5% was evaluated as "bad". The results are shown in Table 1. The number of squares where peeling occurred in the laminated film of Example 1 was 0. The number of squares where peeling occurred in the laminated film of Comparative Example 1 was 82.
[0121] [evaluation] In the laminated film of Example 1, in the C1s spectrum at an analysis depth of a carbon element ratio of 25 atom% in the X-ray photoelectron spectroscopy analysis of the inorganic layer, the intensity Icc of the peak derived from the C-C bond, the intensity Ico of the peak derived from the C-O bond, and the intensity Icoo of the peak derived from the O=C-O bond satisfied (Ico+Icoo) / Icc≧0.5, and the value of the formula was 0.72. This indicates that in the boundary region (interface and its vicinity) between the substrate film and the inorganic layer, there are relatively many chemical bonds formed between the substrate film and the inorganic layer via the CO- and O=C-O- moieties of the resin component derived from the substrate film. Therefore, in the laminated film of Example 1, the adhesion of the inorganic layer was ensured.
[0122] In contrast, in the laminated film of Comparative Example 1, in the C1s spectrum at an analysis depth of a carbon element ratio of 25 atom% in the X-ray photoelectron spectroscopy analysis of the inorganic layer, the intensity Icc of the peak derived from the C-C bond, the intensity Ico of the peak derived from the C-O bond, and the intensity Icoo of the peak derived from the O=C-O bond did not satisfy (Ico+Icoo) / Icc≧0.5, and the value of the same formula was 0.46. This indicates that in the boundary region (interface and its vicinity) between the base film and the inorganic layer, the chemical bonds formed between the base film and the inorganic layer via the CO- and O=C-O- moieties of the resin component derived from the base film are significantly less than those in Example 1. Therefore, the adhesion of the inorganic layer could not be ensured in the laminated film of Comparative Example 1.
[0123] [Table 1] [Explanation of symbols]
[0124] X Laminated Film H Thickness direction D plane direction 10. Base film 10a 1st page 10b 2nd side 11 Resin film 12 Cured resin layer 20 Inorganic layer 21 Adhesion layer 22a, 22c High refractive index layer 22b, 22d Low refractive index layer
Claims
1. A laminated film comprising a base film and an inorganic layer on the base film, A laminate film, in which in a C1s spectrum at an analysis depth with a carbon element ratio of 25 atom % in an X-ray photoelectron spectroscopy analysis of the inorganic layer in a thickness direction from the opposite side to the base film to the base film side, a peak intensity Icc at 285 eV derived from a C-C bond, a peak intensity Ico at 286.5 eV derived from a C-O bond, and a peak intensity Icoo at 289 eV derived from an O=C-O bond satisfy (Ico+Icoo) / Icc≧0.
50.
2. The laminate film according to claim 1, wherein in the C1s spectrum, the intensity Ioc of the peak at 288 eV derived from a C=O bond, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy Ioc / (Icc+Ico+Icoo)≦0.
01.
3. 2. The laminate film according to claim 1, wherein in a C1s spectrum at an analysis depth of a carbon element ratio of 55 atom% in the X-ray photoelectron spectroscopy analysis, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy (Ico+Icoo) / Icc≧0.
80.
4. 2. The laminate film according to claim 1, wherein in the C1s spectrum of the X-ray photoelectron spectroscopy at an analysis depth with a carbon element ratio of 55 atom%, the intensity Ioc of the peak at 288 eV derived from a C=O bond, the intensity Icc, the intensity Ico, and the intensity Icoo satisfy Ioc / (Icc+Ico+Icoo)≦0.
01.
5. The laminated film according to claim 1 , wherein the inorganic layer contains at least one element selected from the group consisting of In, Si, Cr and Nb.
Citation Information
Patent Citations
Film deposition system, water vapor oxygen barrier stacked body, optical functional filter, and optical display device
JP2010018881A
Water-repellent transparent film, production method of water-repellent transparent film, display and optical adjustment film
JP2019111801A
Gas barrier film, lighting device and display device
WO2017086034A1
Protective film and wavelength conversion sheet
WO2017086319A1
Optical film with antifouling layer
WO2022014572A1